ANALISIS KERJA ARUS KAS PERBANKAN DAN PENGARUHNYA TERHADAP FINANCIAL DISTRESS PERBANKAN BUMN YANG TERDAFTAR DIBURSA EFEK INDONESIA TAHUN 2011-2013 - Effendi, Syahril (Universitas Riau Kepulauan, 2014)
The development of business activities from time to time to know whether the company is progressing or to deterioration, and it is known financial situation at any given moment. Such information can be obtained from the financial statements. The financial statements can also be to be able to assess the results achieved by the company during the future. The existence of the global economic crisis that occurred in the year 2011-2013 is an event in which all sectors of the world market economy collapse or degresi and affect other sectors around the world. the fluctuations in economic activity in Indonesia prior to the increase and decrease of fuel oil (BBM) and the warming of the political conditions, fluctuations in the Composite Stock Price Index (CSPI), exchange rate fluctuations, can result in a decrease of interest in investing in Indonesia can identify less controlled economy, the special the banking company that is more sensitive than a manufacturing company, then the risks of changes in social and political dynamics can result in losses. Therefore, the authors are interested in doing research on the description above, and therefore the study authors mentuangkan under the heading